Meat pies with superfoods linen flour - Galenko, Oleg; Golovachko, Valery (My University, 2020)
Today there is only one plant, 100 g of which is enough to provide a person with full nutrition for the whole day. These are flax seeds. That is why flax seeds and its beneficial properties are so widely used in medicine - in both traditional and folk.
Keywords: кафедра технології м’яса і м’ясних продуктів; meat pies; flax flour; vegetable proteins; trace elements; м'ясні пиріжки; лляне борошно; рослинні білки; мікроелементи